2012
DOI: 10.1186/1472-6890-12-1
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of glycol and toxic alcohol ingestion: utility of anion and osmolal gaps

Abstract: BackgroundPatients ingesting ethylene glycol, isopropanol, methanol, and propylene glycol ('toxic alcohols') often present with non-specific signs and symptoms. Definitive diagnosis of toxic alcohols has traditionally been by gas chromatography (GC), a technique not commonly performed on-site in hospital clinical laboratories. The objectives of this retrospective study were: 1) to assess the diagnostic accuracy of the osmolal gap in screening for toxic alcohol ingestion and 2) to determine the common reasons o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 50 publications
0
59
0
1
Order By: Relevance
“…This method requires expensive equipment and educated technical staff; therefore, ethanol is generally measured with the enzymatic method. In some laboratories, the enzymatic method is not possible, and so the calculated osmolal gap provides a practical approach, but it must be remembered that there are several conditions that can increase the osmolal gap other than ethanol, such as diabetes mellitus, dehydration, or hypernatremia [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…This method requires expensive equipment and educated technical staff; therefore, ethanol is generally measured with the enzymatic method. In some laboratories, the enzymatic method is not possible, and so the calculated osmolal gap provides a practical approach, but it must be remembered that there are several conditions that can increase the osmolal gap other than ethanol, such as diabetes mellitus, dehydration, or hypernatremia [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study reported the sensitivity and specificity of the osmolal gap for toxic alcohol ingestion to be 0.82 and 0.85, respectively, with a cutoff of Ͼ14 mOsm/kg (10 ). Other causes of increased osmolal gap that should be considered include alcoholic and diabetic ketoacidosis (acetone accumulation), renal failure, shock, and mannitol infusion (10 ).…”
Section: Methanol Toxicitymentioning
confidence: 99%
“…[46][47][48][49][50][51][52][53][54][55] Knowing, however, that the normal range for osmolar gap can be as low as À5 or À10 mOsm, it is possible for a patient to present with a toxic ingestion and an osmolar gap that is within the reference range but actually represents a significant change from their normal baseline. For example, a patient with a pre-existing osmolar gap of À5 mOsm who then ingests ethylene glycol and has a blood ethylene glycol concentration of 50 mg/L may only increase their osmolar gap to 5 mOsm which remains below the reference interval of 10 mOsm.…”
Section: -4952-57mentioning
confidence: 99%
“…There have been more than 15 different formulae proposed and the validity of each of these has long been debated. [46][47][48][49][50][51][52][53][54][55] Most of the formulae in widespread use include contributions from sodium, urea and glucose with a few including ethanol. 45 In general, the variability of each of these formulae is explained by differing coefficients for the relative contribution of each of the substrates.…”
Section: Indirect Testingmentioning
confidence: 99%